Low‐coordination Nanocrystalline Copper‐based Catalysts through Theory‐guided Electrochemical Restructuring for Selective CO2 Reduction to Ethylene - Fang, Wensheng; Lu, Ruihu; Li, Fu‐Min; He, Chaohui; Wu, Dan; Yue, Kaihang; Mao, Yu; Guo, Wei; You, Bo; Song, Fei; Yao, Tao; Wang, Ziyun; et al. (Angewandte Chemie International Edition, 2024)
Revealing the dynamic reconstruction process and tailoring advanced copper (Cu) catalysts is of paramount significance for promoting the conversion of CO2 into ethylene (C2H4), paving the way for carbon neutralization and facilitating renewable energy storage. In this study, we initially employed density functional theory (DFT) and molecular dynamics (MD) simulations to elucidate the restructuring behavior of a catalyst under electrochemical conditions and delineated its restructuring patterns. Leveraging insights into this restructuring behavior, we devised an efficient, low‐coordination copper‐based catalyst. The resulting synthesized catalyst demonstrated an impressive Faradaic efficiency (FE) exceeding 70 % for ethylene generation at a current density of 800 mA cm−2. Furthermore, it showed robust stability, maintaining consistent performance for 230 hours at a cell voltage of 3.5 V in a full‐cell system. Our research not only deepens the understanding of the active sites involved in designing efficient carbon dioxide reduction reaction (CO2RR) catalysts but also advances CO2 electrolysis technologies for industrial application. Based on the electrochemical restructuring calculation of Cu catalysts, a customized, low‐coordination Cu catalyst was prepared for the efficient electrocatalytic reduction of CO2 to ethylene. Benefiting from this excellent catalyst, the selectivity of CO2 conversion to ethylene reached 72% at a current density of 800 mA cm−2, with a durable stability of 230 hours in an electrolyzer.